(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
This Study is carried out in two plastic green houses in Banias region (Al-Basiah) during 2020-2021 Agricultural season, Aimed to evaluate Incidence and Severity of Cladosporium fulvum on Tomatoes within 55 days after tomato planting. A laboratory study was also conducted in Agriculture collage laboratories Tishreen University and included fungus isolating on PDA medium and effects of temperatures on fungus growth. Results indicated that olive mold disease is widespread on Tomatoes plastic green houses with Incidence ranged from 40.77 to 43.94% and Severity ranged from 31.57 to 36.10%. At results of laboratory study the fungus colony on PDA medium has a regular circular shape of the edges, with olive green center and conidia spores was interconnected in black brown chain, divided into two or three cells. Temperature affects fungus development on PDA medium where the highest daily growth ratio 3.95 mm/day by incubation on 25C°. This indicates that micro climate within tomatoes plastic greenhouses fits growth of disease for most of the year’s month. Key words: Olive mod – Tomatoes – Severity – Incidence.